Stimulatory effect of medium components on phytase production by Aspergillus niger and biotechnological application as a poultry feed additive: DOI: 10.48129/kjs.17947 - Mahmood, Shahzad; Memuna G. Shahid; Muhammad Nadeem; Muhammad S. A. Ahmad; Muhammad Irfan (Kuwait Journal of Science, 2022)
The present study deals with the production of phytase from Aspergillus niger using solid-state fermentation (SSF). Appropriate concentration of different components of the growth medium played an important role for the higher production of phytase. Maximum enzyme activity (265 IU/g) was obtained, when the fungus was grown in the fermentation medium containing, (% w/w) glucose 1, NH4NO3 0.5, MgSO4.7H2O, KCl and FeSO4.7H2O 0.1 each, after 5 days of incubation time using pH 6 at 35 °C incubation temperature. Phytase produced during present study was also supplemented as poultry feed additive and given to broiler chickens for 5 weeks. The results exhibited that there was increase in body weight gain (BWG) of chicks for experimental group T3 (3240 g) in comparison to control group (2090 g). The current study indicated that phytase can effectively be supplemented in the broilers diet for better growth performance, recommending the use of phytase as useful additive in poultry feed formulation.